Gerakan Ekonomi Keagamaan dan Politik Identitas Muslim Pedesaan: Studi di BMT Dana Akhirat Kecamatan Arjasari Kabupaten Bandung - Firman Nugraha (Jurnal Bimas Islam, 2018)
The purpose of writing this article is to describe how the Islamic economy in the form of Baitul Maal wat Tamwil can portray itself as a representation of economic social movements in rural Moslems. The economic social movement is sustained by the Islamic identity politic in rural areas. Being a pious Moslem is the dream of every one. The one of characteristics of kaaffah in religion is to apply the values ​​of Islam in all life dimensions including in the economy activity. With the study setting in Arjasari sub-districtBandung Regency and focus of this study is collectiving action on members of BMT Beyond Funds. The study was carried out through observation and interviews. The result of study shown there is a role of political identity in the success of BMT Beyond Funds as a movement of Islamic finance amid the economic struggle of rural Moslem agriculture in Arjasari. The Islamic identity politic appears in the social structure of rural communities with the majority of Moslems. The power of identity politic also gets a place through awareness, strategy and legitimacy. Tujuan penulisan artikel ini untuk mendeskripsikan bagaimana ekonomi Islam yang secara akademik lebih dikenal dengan ekonomi syariah dalam wujud baitul maal wat tamwil dapat memerankan dirinya sebagai representasi gerakan sosial ekonomi Islam bagi muslim perdesaan. Gerakan sosial ekonomi Islam ini sendiri ditopang oleh politik identitas Islam di perdesaan.Menjadi Muslim yang kaaffah, adalah dambaan setiap umat Islam.Salahsatu ciri kaaffah dalam beragama adalah menerapkan nilai-nilai agama Islam dalam seluruh dimensi kehidupan tidak terkecuali dalam perekonomian. Dengan setting kajian di Kecamatan Arjasari Kabupaten Bandung serta fokus kajian pada BMT Dana Akhirat, dimana studi dilakukan dengan observasi dan wawancara, dapat ditunjukkan bahwa ada peran politik identitas dalam keberhasilan BMT Dana Akhirat untuk menjadi oase pembiayaan syariah ditengah pergulatan ekonomi pertanian Muslim perdesaan di Arjasari. Politik identitas Islam tampak dalam struktur sosial masyarakat pedesaan dengan mayoritas beragama Islam.Kekuatan politik identitas ini juga mendapatkan tempat melalui kesadaran, strategi dan legitimasi